Learning to Make Hydroponic-Based Animal Feed - Emay Mastiani; Farhan Ilham Wira Rohmat; Dadang Solikhin; Mega Mentari Rahayu (Postgraduate, University of Mataram, 2023)
Mild intellectually disabled is an individual who has intelligence far below the average individual in general. Although the intellectually disabled have intelligence that is far below the average, their abilities can be optimized and empowered through learning simple skills that do not require complex thinking or semi-skills. Hydroponic-based animal feed production is an activity in the semi-skills category that has the potential to be used as a medium for learning and empowering the intellectually disabled. This study aims to evaluate the potential of hydroponic-based animal feed production activities as a medium of learning and empowerment to improve the ability and physical suitability of the intellectually disabled. The research method used is field testing and Research and Development (R&D), and data is obtained through observation, interviews, and Focus Group Discussions (FGD). We found that the intellectually disabled can perform stages of work in the manufacture of hydroponic-based animal feed, the introduction of tools and materials, the manufacture of animal feed, the maintenance of tools and materials, and the maintenance of results. The results showed that every step in hydroponic-based animal feed production activities had been implemented and could be used as a medium of learning and empowerment to optimize and empower the intellectually disabled.